Hello, year! - Jacobs, Leland B. (Leland Blair), 1907-; Aloise, Frank E. (Champaign, Ill., Garrard Pub. Co., 1972)
Sixty-two poems by various authors on such subjects as the seasons, holidays, and the weather.
11 13 26 39
Keywords: Children's Poetry; American poetry -- Collections